Clinical and laboratory characteristics and prognosis of patients with hepatocellular carcinoma - Chuyen, Nguyen Thi Hong; Duong, Tran Anh Thuy; Giang, Nguyen Thi Thu; Quyen, Tran Thi; Phuong, Phung; Thuan, Dang Cong; Cau, Nguyen Van; Huan, Nguyen Tran Thuc; Phuc, Nguyen Thanh; Huy, Le Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
ABSTRACT Purpose: We investigated the influence of baseline characteristics of patients with hepatocellular carcinoma (HCC) on prognosis. Methods: A Retrospective descriptive study on patients with HCC was carry out at the Oncology Department of Hue University of Medicine and Pharmacy Hospital and Hue Central Hospital (HCH), Viet Nam, from Oct 2015 to Dec 2019. Demographic, laboratory, tumor characteristics, and performance status were determined before treatment. Predictors of survival were identified using the Kaplan - Meir test and the Cox model. Result: A total of 261 patients, 87.4% male; median age was 58.4; 80,1% of patients admitted to hospital because of right upper quadrant pain. 45.2% ECOG 0, 51.7% ECOG 1; AFP > 400 ng/mlhas 67.4%. The most robust predictors of survival were tumor size, ECOG, portal vein tumor thrombus, Barcelona Clinic Liver Cancer (BCLC), initial treatment. Overall survival in patients with HCC was 9.0 months. In a multivariate analysis: BCLC and initial treatment modalities were independent predictors of survival. Conclusions - Patients with HCC had a poor survival with a median of nine months. Five easily measurable clinical variables were significant predictors of survival in patients with HCC.